EFFECTIVENESS OF TRANSCUTANEOUS BILIRUBIN (TCBR) MEASUREMENT IN HIGH RISK NEONATES AND TO EVALUATE THE VALIDITY OF TRANSCUTANEOUS BILIRUBIN (TCBR) WITH TOTAL SERUM BILIRUBIN (TSBR) LEVELS IN BOTH LOW AND HIGH RISK NEONATES AT A TERTIARY CARE CENTER OF A DEVELOPING COUNTRY - Durre Shahwar; Sabina Ariff; Batha Tariq; Arjumand Rizvi; Syed Rehan; Ali Shabbir Hussain (Pakistan Armed Forces Medical Journal, 2021)
Objective: To evaluate the utility of a Transcutaneous Bilirubin nomogram in high risk neonates and to evaluate the validity of Transcutaneous Bilirubin and Total serum bilirubin in both low and high-risk neonates.